Food security and translocal livelihoods in high mountains: evidence from Ladakh, India - Dame, Juliane (Mountain research and development, 2018)
Reducing food insecurity is crucial to sustainable development in mountain regions. Case studies on complex food systems in these areas facilitate depiction of current trends and challenges and provide detailed information to policymakers. Based on empirical research in Ladakh in the Indian Trans-Himalaya, this study assesses livelihood dynamics in the context of rapid socioeconomic changes and aims to show how diverse spatial and temporal patterns of mobility shape strategies of the mountain population. The results exhibit translocal livelihood diversification as an emerging reality. The consequences are a reduction in land-based food production and an increased reliance on markets and government food subsidies. This shift to a supply-oriented food system implies gender- and intergenerational-biased challenges, such as growing socioeconomic disparities, new dependencies, and an erosion of social institutions in the rural communities. Moving beyond the focus on land-based food production, this article sheds light on the interaction between agriculture, mobility, markets, and supplies, and highlights the need for cross-sectoral policy approaches to meet the challenge of food insecurity in mountains.
Gesehen am 12.03.2019